Werbewirkungsforschung mit Bezug auf die Fernsehwerbung - Pungor Martina (2016)
My thesis focuses on the research into the impact of TV advertising. My personal interest in the topic was kindled by the ubiquity of advertising, so I was motivated to delve into it by examining the impact of advertising in order to find out how advertisements and commercials influence our life. If we want to sell a product or a service by promoting it, first it is advisable to plan our approach. In my paper I set out to investigate advertisements in this light. In the theoretical part of my paper the basic concepts and terms related to advertising are explained. Detailed attention is devoted to describing the forms and objectives of adver-tising and a more thorough explanation from the perspective of economic psychology is at-tempted concerning both the functions of advertisements and the models of the effects of advertising. Commercials primarily aim to catch our attention. Accordingly, in my paper I set out to explore how certain effects can influence our buying decision. Advertisements can be made effective by appropriately applying certain impact models, thus the desired results can eventually be achieved. The main part of my paper examines the ways of how successful ad-vertisements are created. The object of my investigation is analysed with the help of several researches. It is along the line of these researches and my interpretation of them that I attempt to answer the ques-tions that were raised during the process. The diagrams are included as evidence as well as to make the work more comprehensible and interesting. The main objective of the thesis is to analyse and interpret the impact of TV commer-cials. The central question revolves around the role of TV commercials as well as their func-tions, techniques, types and effects. An additional aim of the present paper is to throw light on the ways of how these com-mercials can be made effective. As the number of TV commercials is growing steadily, I think the issue should not be ignored. The conclusion of my research reveals that efficient advertisements are able to influence our buying decision and will eventually lead to a definite intention of purchase. As a final remark it can be said that there is a good reason that we cannot imagine our life without ad-vertisements.